Isolasi dan Identifikasi Bakteri Penyebab Bau Kaki - Vernanda, Renna Yulia; Ariyanti, Agnes Dwi; Oktaviana, Claudia; Gunawan, Firman Sandi; Prastica, Yohana Maria Vianney; Mauryn, Flora Raliana; Rati, Angelica Krisensiani; Hasfayo, Fridolin Putri; Ribeiro, Margareta Vita (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2023)
Foot odour is caused by combination of sweat and bacteria. Smelly feet can lead to lack of confidence and discomfort. In this study, conducted on 21 probands to isolate the microbes with the following criteria: male, aged 18-25 years, wore shoes for 8 hours without taking them off, moist, and smelly feet. Isolating microbes from the feet using a cotton swab. The result of the study found 7 isolates. Several bacteria isolates, namely: Staphylococcus sp, Bacillus sp, Enterobacter sp. In addition, isolates from fungi Aspergillus sp, Penicillium sp, Syncephalastrum sp, and Candida krusei yeast were isolate